Implementation of Administrative Management Functions in the General Section of the Bantaeng Regency BKPSDM Office (Pinisi Journal of Officers Review, 2024)
The administrative management function in this research area provides empirical and theoretical concepts so that it can improve administrative performance at the general office of BKPSDM Bantaeng Regency as well as describe and support and inhibiting factors. The research methods used are qualitative descriptive, interviews and documentation. The implementation of the administrative management function of the Bantaeng Regency BKPSDM has improved administrative performance quite well even though it is not in accordance with what is expected. (a) Planning is recognized by compiling work programs, recruiting employees, striving for a competent workforce and adequate facilities and infrastructure as well as the division of labor in accordance with their respective competencies, (b) Organizing is recognized by the division of duties and responsibilities, preparation and presentation of employee data, mutations and promotions that are recognized in accordance with employee competencies, as well as discipline that must be maintained; (c) Actuating is acknowledged by the way the leadership participates in the process of being involved in the process such as providing direction through coaching or instruction so that the form of filing, correspondence, disposition, and SKP can be implemented properly; (d) Supervision/Controlling is recognized using e-performance applications. The supporting factors for administrative management to improve the administrative performance of the Bantaeng Regency BKPSDM are good cooperation between employees, communication ethics and facilities and infrastructure, while the inhibiting factors are the limitations of the ability and skills of employees, especially in using electronic media and the lack of awareness of employees to improve their abilities, the findings of this research are the skills of employees, especially in the use of electronic media need boosted.